Factors Influencing Cloud Computing Adoption-Compared Review and A 4-M Recommendation - Nguyen, Giang Thi; Liaw, Shu-Yi; Augustin, Jean-Luc Pradel Mathurin; Vu, Hien Thi (Journal of Future Internet, 2021)
Cloud computing is increasingly popular in firms around the world. However, there are limited review studies focusing on cloud computing applications in companies. Thanks to the application of the technology-environment-organization (TOE) framework and diffusion of innovation (DOI) theory, this research unearths the factors influencing the decision-making process in cloud computing between developed and developing countries. The review further captures the stonewalls of cloud computing adoption enlisted in literature. Systematic review methods were applied to analyze relevant articles during the 2011 to 2020 period. The findings reveal that 36 factors impact organizational cloud computing adoption, out of which 21 factors occur in both developed and developing economies. The remaining 15 factors differ between developed and developing countries. Five of these factors that reveal a strong impact on cloud adoption by firms are Technology readiness, Top management support, Relative advantage, Costs, and Security, privacy and ethics concern. The literature-based limitations found in previous studies on cloud computing adoption in firms include research area, data collection technique, research methodology and theoretical models, and research subject. These challenges were organized in a 4-M recommendation for future research.